Invasion of the Hawaiian Islands by a parasite infecting imperiled stream fishes. Issue 3 (19th May 2017) - Gagne, Roderick B.; Sprehn, C. Grace; Alda, Fernando; McIntyre, Peter B.; Gilliam, James F.; Blum, Michael J.
Abstract : Points of origin and pathways of spread are often poorly understood for introduced parasites that drive disease emergence in imperiled native species. Co‐introduction of parasites with non‐native hosts is of particular concern in remote areas like the Hawaiian Islands, where the introduced nematode Camallanus cotti has become the most prevalent parasite of at‐risk native stream fishes. In this study, we evaluated the prevailing hypothesis that C. cotti entered the Hawaiian Islands with poeciliid fishes from the Americas, and spread by translocation of poeciliid hosts across the archipelago for mosquito control. We also considered the alternative hypothesis of multiple independent co‐introductions with host fishes originating from Asia. We inferred conduits of introduction and spread of C. cotti across the archipelago from geographic patterns of mtDNA sequence variation and allelic variation across 11 newly developed microsatellite markers. The distribution of haplotypes suggests that C. cotti spread across the archipelago following an initial introduction on O'ahu. Approximate Bayesian Computation modeling and allelic variation also indicate that O'ahu is the most likely location of introduction, from which C. cotti dispersed to Maui followed by spread to the other islands in the archipelago. Evidence of significant genetic structure across islands indicates that contemporary dispersal is limited. Our findings parallel historical records of non‐native poeciliid introductions and suggest that remediating invasion hotspots could reduce the risk of infection in native stream fishes, which illustrates how inferences on parasite co‐introductions can improve conservation efforts by guiding responses to emerging infectious disease in species of concern.